Metaphor, Modularity, and the Evolution of Conceptual Integration. - Chiappe, Dan L. (Metaphor & Symbol, 2000)
We integrate information from distinct domains, especially in metaphor. What sort of cognitive architecture underlies this kind of integration? Fodor (1983) argued that it involves nonmodular mechanisms. He also contended that the nonmodular mechanisms evolved from modular ones through a process of demodularization, a position elaborated by Mithen (1996). In this article, I defend Fodor and Mithen from criticisms offered by Sperber (1994). Sperber suggested that nonmodular mechanisms are unlikely to have evolved because an increasingly large database would incapacitate the cognitive system due to combinatorial explosion and the frame problem. Moreover, he argued that nonmodular mechanisms are not required to explain our ability to integrate information. I argue that proponents of demodularization can respond to Sperber's criticisms by assuming that either an expanding database co-evolved with increasingly sophisticated search mechanisms or the cognitive system evolved along connectionist lines. Moreover, I argue that Sperber's modular account of conceptual integration fails to satisfy the criteria for modularity-namely, information encapsulation.